Recent Advances in Sharding Techniques for Scalable Blockchain Networks: A Review - Brandon Liew Yi Quan; Nur Haliza Abdul Wahab; Arafat Al-Dhaqm; Ahmad Alshammari; Ali Aqarni; Shukor Abd Razak; Koh Tieng Wei (IEEE Access)
Blockchain is a technology that has gained popularity in recent years due to its immutability and decentralized features. Various industries have started integrating this technology into their business models, resulting in the development of various types of blockchain networks. This paper reviews the latest academic advancements in sharding techniques within the various types of sharded blockchain networks implemented in the past five years to identify their strengths and weaknesses. The increasing volume of transactions in blockchain networks has caused issues in terms of scalability, transaction efficiency, storage, and security, which obstruct the global adoption of blockchain technology. Sharding in blockchain is a solution that aims to address these issues through various types of sharding techniques, such as network, transaction, or state sharding, along with the various types of networks and systems. The general definition of sharding is the partitioning of the network into subsets known as shards, which allows them to validate transactions in parallel, resulting in performance and scalability improvements of the existing network. The existing sharding techniques (before 2020) and the latest sharding techniques (2020–2024), along with their characteristics, advantages, and disadvantages, are also discussed. An analysis based on the performance evaluation of recent sharding techniques was conducted to further understand the impact of these techniques. The result of the review provides critical insights into the advancements in sharding techniques and fosters innovation while facilitating the widespread adoption of sharding-based solutions in the blockchain ecosystem.